2008
DOI: 10.1017/s1751731108003182
|View full text |Cite
|
Sign up to set email alerts
|

Levels of copper and zinc in diets for growing and finishing pigs can be reduced without detrimental effects on production and mineral status

Abstract: One hundred and sixty pigs were used to evaluate dietary copper (Cu) and zinc (Zn) supplementation on performance, fecal mineral levels, body mineral status and carcass and meat quality. Diets differed in mineral form (MF) (Cu and Zn in the form of proteinate amino acid chelate (organic) or sulfate (inorganic)) and inclusion level (IL) (27 mg/kg of total Cu and 65 mg/kg of total Zn ('low') or 156 mg/kg of total Cu and 170 mg/kg of total Zn ('high')) according to a 2 3 2 factorial arrangement of treatments. Pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
0
11
0
2
Order By: Relevance
“…In this experiment, all foxes were fed the same basal diet with Cu and Zn supplementation. We believe that the effect of their addition on palatability was limited as the supplemented amount was relatively low compared with supplemental levels in pigs [29]. Li et al [30] reported that high dietary Cu (125 and 250 mg/kg) appears to increase feed intake and promote weight gain by enhancing the neuropeptide Y (NPY) concentration and NPY mRNA expression level in the hypothalamus of pigs.…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, all foxes were fed the same basal diet with Cu and Zn supplementation. We believe that the effect of their addition on palatability was limited as the supplemented amount was relatively low compared with supplemental levels in pigs [29]. Li et al [30] reported that high dietary Cu (125 and 250 mg/kg) appears to increase feed intake and promote weight gain by enhancing the neuropeptide Y (NPY) concentration and NPY mRNA expression level in the hypothalamus of pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc oxide supplied at pharmacological level evidently improves weaned pig performance and is cheap what may led to inappropriate usages, environmental Zn accumulation and increase of bacterial resistance. Hernandez et al (2008) have demonstrated that the use of dietary Cu and Zn organic complexes, which show higher bioavailability, enabled to obtain increased improvement of the performance of pigs in comparison to that observed in the animals receiving supplementation with inorganic sources of these metals. For example, Zn in TM bioplexes may be used in concentrations of 100 and 250 mg/kg feed still showing some positive impact on piglets growth (Mullan et al 2007).…”
Section: Future Perspectives Of Using Minerals As Alternatives To Conmentioning
confidence: 99%
“…It was found that the source of supplemental Zn did not influence plasma Zn concentration [32]. Also Hernández et al (2008) pointed that the concentration of Cu and Zn in the blood of pigs fed with the organic form of these microelements as proteinate amino acid chelate was higher by 4% and 11%, respectively, compared to the blood of pigs, the diet of which was supplemented with such inorganic form as sulfate after 77 days of the experiment (the total content of Cu and Zn in feed was 156 mg kg -1 and 170 mg kg -1 , respectively) [33]. In the study of Wedekind et al (1994), the concentration of Zn in the plasma of pigs was similar for all tested forms of zinc: zinc-methionine complex, zinc-lysine complex and ZnSO 4 ·H 2 O.…”
Section: The Mineral Composition Of Bloodmentioning
confidence: 99%
“…The content of Zn in liver of weanling pigs in the ZnOrg group was slightly lower than in ZnSO 4 ·7H 2 O (for the Zn level 10 and 20 mg kg -1 of feed it was a decrease by 9.5% and 3.0% respectively) [32]. Also Hernández et al (2008) pointed out that the content of Cu and Zn in the liver of pigs fed with the organic form of such microelements as proteinate amino acid chelate was lower by 12% and 3%, respectively than in the liver of pigs, the diet of which was supplemented with an inorganic form as sulfate, after 77 days of the experiment (the total content of Cu and Zn in feed was 156 mg kg -1 and 170 mg kg -1 respectively) [33]. However, Apgar et al (1995) found that the supplementation of the organic form of Cu in the diet of weanling pigs in the form of the copper-lysine complex caused an increase in Cu content in liver by 102% when compared with CuSO 4 [36].…”
Section: The Mineral Composition Of Livermentioning
confidence: 99%